Change and continuity in translation. Renewing communication in a globalized world - Gambier Yves (Lithuania, 2022)
At first sight, technology is transforming rapidly the workflow in translation. Like in many other fields, digital technology impacts translators’ daily life. Technology is so omnipresent that we are hardly capable of measuring the consequences it had, the metamorphosis it has induced. On the other hand, we are also so fascinated by all the technical devices and platforms we can use that we tend to forget or undermine the past and how technology and media have always played a role in the evolution of our cultures. Looking back in history, we can realise that some current practices in translation, considered as new, are not really so new.
The use of multimodal “texts” we are referring to everyday is not without analogy with the production and the reading of “texts” in the past. Perhaps the transition from a logocentric to an intersemiotic and intermedial culture puts an end to a limited period of time in history, dominated by printing. But closing the “Gutenberg parenthesis” does not imply coming across the same artefacts again as before the 15th century.
Based on the existing literature, our paper questions the borders between some translation practice, media, disciplines, through an historical perspective.